The Design and Development of Smart Agriculture Data Analytics - Marjudi, Suziyanti; Setik, Roziyani; Salamat, Mohamad Aizi; Yusfaidir, Muhammad Fahruddin Irfan (Ijetea, 2023)
Agriculture is on the verge of entering the Smart Farming era, in which farming operations will become digitalized and data-driven, allowing for better decision support, smart analytics, and forecasting. Farming is the most diverse economic sector and is critical to a country's overall economic development. The Internet of Things (IoT) can potentially optimize agriculture and farming sector activities by reducing manpower through technology. Forecasts are central to most agricultural and agricultural-related operations. Smart Agriculture Data Analytics (SADA) was developed to address this issue. SADA is an embedded system with two components: data analytics and the Internet of Things (IoT). IoT in SADA also assists farmers in collecting data and learning more about the appropriate soil PH scale, fertilizer dataset, air humidity, and temperature. A prototyping model is used in software development. The farmer can provide real-time feedback, request project changes, and update model specifications. SADA will help farmers understand the trend of analytics crop production, allowing them to increase yield.